Predictors of poor hygiene in Ibadan north local government area of Oyo State (2021)
Poor hygiene has always been a bane and discomfort to the existence of man, the partial origin of diseases, sicknesses and health trauma. The presence of it is so common and usual leaving pathogens in the atmosphere harmful to man. Thus, the need for maintaining good hygiene. This investigated the predictors of poor hygiene in Ibadan North Local Government Area of Oyo State. The descriptive survey research design was used for this study. The questionnaire tagged "predictors of poor hygiene in Ibadan North Local Government Area of Oyo State " was administered to the total sample population of a hundred people which included market men, women, artisans and civil servants who were all residents of lbadan North Local Government Area of Oyo State. Descriptive and inferential statistics were used to analyse the data collected and the results are as follows: it was discovered that the level of hygiene awareness among residents of lbadan North Local Government Area of Oyo Stale was low (Mean=2.32). In addition, it was revealed that the level of hygiene practices among residents of Ibadan was very low. It was also found that there was a significant relationship between illiteracy and poor hygiene (r = 0,770, p< 0.05). It was further discovered that there was a significant relationship between socio-cultural demographic factor and poor hygiene (r = 0.693. p<0.05). In addition. it was found that there was a significant relationship between family background and poor hygiene (r = 0.558, p<0.05). Moreover, it was found that there was a significant relationship between socio-economic Status and poor hygiene (r = 0.709, p<0.05). On this basis, it was recommended that Information should be given in schools, public education and community health centres in Order to promote positive hygiene behaviour